The characteristics and core components needed to implement exercise classes for people with dementia in the community - Long, Annabelle Louisa (2023)
Background Dementia is a significant cause of disability and dependency in adults, and its growing prevalence has produced both individual and societal challenges. Exercise has been identified as an intervention with the potential to provide physical, mental and well-being benefits for those experiencing symptoms of dementia. This thesis explores the proposition that exercising within a group setting may provide benefits beyond the exercise's physiological mechanisms, offering social and support elements that would be absent when exercising alone.